2020
DOI: 10.3389/fimmu.2020.605338
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Memory CD4+ T-Cell Responses in Individuals With Previously Treated Extrapulmonary Tuberculosis

Abstract: Extrapulmonary TB (EPTB) occurs with increased frequency in persons with underlying immunodeficiency. Even after recovery from acute illness, differences in immune phenotype and activation persist. Studies defining characteristics of immune responses after recovery from extrapulmonary TB may provide insights into factors that increase TB risk. We performed two case-control studies (in the United States and Brazil) among HIV-seronegative adults with previous EPTB (n = 9; 25), previous pulmonary TB (n = 7; 25), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The study identified less immigrants among those who have extrapulmonary TB, as well as with positive-microscopy of materials other than sputum. It is known that extrapulmonary TB occurs with increased frequency in persons with underlying immunodeficiency caused by other health conditions such as HIV/AIDS and diabetes mellitus, which were more prevalent in Brazilian natives ( Barreto-Duarte et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study identified less immigrants among those who have extrapulmonary TB, as well as with positive-microscopy of materials other than sputum. It is known that extrapulmonary TB occurs with increased frequency in persons with underlying immunodeficiency caused by other health conditions such as HIV/AIDS and diabetes mellitus, which were more prevalent in Brazilian natives ( Barreto-Duarte et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ T cells can spread EPTB early, promote TB development, and maintain multi-effect functions of CD8+ T and CD3– lymphocytes (Yao et al, 2014 ). Increased memory CD4+ T cell response frequency in previously treated EPTB patients (Barreto-Duarte et al, 2020 ). Research on Memory B and dendritic cells is sparse and awaits our experimental additions.…”
Section: Discussionmentioning
confidence: 99%
“…observed impaired cellular immunity together with increased plasma levels of cortisol and pro‐inflammatory cytokines and reduced DHEA levels in tuberculosis patients and observed increased lympho‐proliferator response and better immune endocrine scenario with anti‐tubercular therapy. In a study done in Brazil, Barreto‐Duark et al 109 . observed higher levels of CD4+ memory T cells, proliferator to Mycobacterium antigens with highest expression of CD19 on active T regulator cells in EPTB cases.…”
Section: Immune Factors In Fgtb and Lgtbmentioning
confidence: 96%